Fatores associados à satisfação do usuário quanto aos cuidados ofertados na Atenção Básica em Saúde: análise a partir do 1º ciclo de avaliação externa do PMAQ-AB - Protasio, Ane Polline Lacerda (2014)
In view of the Primary Health Care in Brazil has been strengthened, mainly, with the new National Primary Care Policy (PNAB), the Brazilian Ministry of Health has created the Program of Improving Access and Quality of Primary Care (PMAQ-AB) that aimed to improve healthcare public service quality and to enhance the Brazilian qualified health services within the SUS (Brazil's Unified Public Health System). By using the Module III of the external evaluation instrument from the 1º cycle of PMAQ-AB, which contains a lot of information on perception and satisfaction of public health services users regard to their access and usage, this present work aims to identify, considering statistical tools, the main factors that influence the user satisfaction of health services in Brazil and in its regions in order to develop decision models to help health public officers to define actions that increase health service quality and to make effective decisions. In this way, this work was carried out considering secondary data from the 1º cycle of PMAQ-AB, which takes place from 2012 to the first half of 2013. It was obtained a descriptive analysis, a cluster analysis to find the dependent variable of user satisfaction and logistic regression was applied in order to obtain decision models for Brazil and its regions. As a result, the main factors associated with user satisfaction on the provided health service for Brazil and its regions were obtained. Considering the results on Brazil as a whole, the achieved main factors were the following: the users perception on the health care unit staff on not solving their health needs (OR = 0.39) and the user does not (OR = 0.44) feel respected by health professionals in relation to their cultural habits, customs, religion or feel it only a few times (OR = 0.49). It was also noticed that the factors that influence the user satisfaction vary according to the considered region of Brazil due to mainly its diversity. Beyond the factors observed in Brazil, the following factors were also noted in its regions: the health unit time table does not meet the user needs, the users cannot be served when they are in the health care unit unless an previous appointment and the users have difficult to make complaints or suggestions in the health care unit. It was concluded that it is important that health care unit staff and managers try to improve health care unit access, to serve the user needs, to improve organization, and especially to strengthen the link of users and health professionals, in addition to home visits, considering socio-geographic and socioeconomic aspects.